Shared morphological consequences of global warming in North American migratory birds. (4th December 2019) - Weeks, Brian C.; Willard, David E.; Zimova, Marketa; Ellis, Aspen A.; Witynski, Max L.; Hennen, Mary; Winger, Benjamin M.
Abstract: Increasing temperatures associated with climate change are predicted to cause reductions in body size, a key determinant of animal physiology and ecology. Using a four‐decade specimen series of 70 716 individuals of 52 North American migratory bird species, we demonstrate that increasing annual summer temperature over the 40‐year period predicts consistent reductions in body size across these diverse taxa. Concurrently, wing length – an index of body shape that impacts numerous aspects of avian ecology and behaviour – has consistently increased across species. Our findings suggest that warming‐induced body size reduction is a general response to climate change, and reveal a similarly consistent and unexpected shift in body shape. We hypothesise that increasing wing length represents a compensatory adaptation to maintain migration as reductions in body size have increased the metabolic cost of flight. An improved understanding of warming‐induced morphological changes is important for predicting biotic responses to global change.